2016
DOI: 10.1016/j.polymer.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Control of inclusion size and toughness by reactivity of multiblock copolymer in epoxy composites

Abstract: In this paper, the strategy to achieve high fracture toughness and impact strength of epoxy blends by introducing a new family of reactive block copolymer (RBCP), poly[styrene-alt-(maleic anhydride)]block-polystyrene-block-poly(n-butyl acrylate)-block-polystyrene, with different reactivity is reported. Inclusions size of RBCP in cured blends was controlled from nanometer to micrometer by simply adjusting the fraction of reactive block in RBCP. The systematical study on the structure-property relationship revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
(69 reference statements)
2
12
0
Order By: Relevance
“…55 The innovative reactive blending work of He and his group provides an insight on developing toughened epoxy thermosets utilized for both high and low fracture rates. 56 With the introduction of a new family of reactive block copolymer, poly[styrene-alt-(maleic anhydride)]-block-polystyrene-block-poly(n-butyl acrylate)-block-polystyrene, with different reactivity in epoxy blends, they were able to control the inclusion size of reactive block copolymer in cured blends from nanometer to micrometer by simply adjusting the fraction of the reactive block in reactive block copolymer. The systematic study on the structure-property relationship revealed that the thermal and mechanical properties of modified blends strongly depend on inclusion size.…”
Section: Toughness Enhanced Resinsmentioning
confidence: 99%
“…55 The innovative reactive blending work of He and his group provides an insight on developing toughened epoxy thermosets utilized for both high and low fracture rates. 56 With the introduction of a new family of reactive block copolymer, poly[styrene-alt-(maleic anhydride)]-block-polystyrene-block-poly(n-butyl acrylate)-block-polystyrene, with different reactivity in epoxy blends, they were able to control the inclusion size of reactive block copolymer in cured blends from nanometer to micrometer by simply adjusting the fraction of the reactive block in reactive block copolymer. The systematic study on the structure-property relationship revealed that the thermal and mechanical properties of modified blends strongly depend on inclusion size.…”
Section: Toughness Enhanced Resinsmentioning
confidence: 99%
“…These suggest that under LOPB content lower than 20 wt % in the blends the LOPB particles were relatively evenly distributed throughout the epoxy matrix to obtain more homogeneous particle size/distribution which was considered playing an important role in improving the overall performances of epoxy blends . Similarly, evenly dispersed reactive rubber particles in the matrix in certain range of reactive component addition were found by He et al . and Wang et al, which were attributed to the interfacial compatibilization of in situ reaction between the two phases.…”
Section: Resultsmentioning
confidence: 74%
“…He et al reported their series studies on reactive blends, and they found that the addition of 10 wt % reactive block copolymers (BCPs) into the epoxy resins led to considerable improvements in the toughness, imparting nearly a 70% increase in Kc . In their more systematical study, the reactivity and amount of BCPs were found influencing their inclusion sizes in epoxy matrix, and the blends achieved substantially increase in toughness and impact without loss in T g by proper controlling the amount of BCPs with tailored reactivity . Furthermore, these BCPs were synthesized as unimodal reactive core‐shell particles to blend with epoxy, and at an amount of 8%, these particle could be well dispersed in the epoxy matrix and the blends could be greatly toughened with simultaneous improvement in T g .…”
Section: Introductionmentioning
confidence: 99%
“…found that compared with the pure PLA, the impact toughness of PLA/EPB blend was improved by 13 times, while the tensile strength still preserved as a level of 77% relative to that of pure PLA; the epoxy group of EPB played a significant role in enhancing compatibility between rubber phase and PLA matrix, due to the formation of graft‐copolymer between EPB and PLA in the curing process, as well as a remarkable decrease in the particle diameter of rubber phase. By introducing reactive block copolymer (RBCP), He et al . found that compared to that of the neat epoxy ( K IC = 0.83 MPa m 1/2 ), the K IC value of the blend reached up to 2.05 MPa m 1/2 when the content of RBCP was added at 15 wt %, suggesting the significant improvement in fracture toughness, and the blend with 5 wt % RBCP was even observed a slight increase in T g .…”
Section: Introductionmentioning
confidence: 99%